ANALISIS PENEGAKAN HUKUM TERHADAP PENGGUNAAN KNALPOT RACING PADA KENDARAAN BERMOTOR DI POLRES METRO JAKARTA SELATAN - Gilang Safrudin, Achmad; Sudarto (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
Many people use racing exhausts which are synonymous with loud noises. When used they will cause several problems for the people around them. Therefore, it is very interesting and important to study further about how the law is enforced regarding the use of racing exhausts on motorized vehicles at the South Jakarta Metro Police, and what obstacles and solutions are faced by the South Jakarta Metro Police to minimize the use of racing exhausts on motorized vehicles in South Jakarta City. To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it can be seen that the process of law enforcement against vehicles that use racing exhausts is through pre-emptive efforts, namely educating the public about legal knowledge, preventive efforts, namely preventing violations of the law, and repressive efforts, namely taking action against perpetrators of violations guided by Law Number 22 Concerning Road Traffic and Transportation. The obstacles experienced by law enforcement officers are the lack of public awareness of traffic regulations; inadequate facilities and infrastructure, and limited number of traffic police members. Meanwhile, the solution to minimize the use of racing exhausts is to improve service and quality in enforcement; increasing outreach and education activities to the community; empowering and increasing human resources; and provide violation reporting services.